Efektivitas Video Berbasis Literasi Sains terhadap Hasil Belajar Mahasiswa - Agustina, Degi Alrinda; Bua, Agustinus Toding; Noviantari, Ika; Irawati, Nina (MASALIQ, 2025)
This research aims to determine the effectiveness of scientific literacy-based videos on student learning outcomes. The scientific literacy-based videos have been validated by material experts, media experts, and language experts. The application of scientific literacy-based learning videos is carried out using blended learning, which integrates learning that combines various physical and virtual sources. The research used a pre-experimental, one-group pre-test-post-test design, namely by giving pre-tests and post-tests to students. Data analysis was carried out by determining N-Gain. The research was carried out using the Google Classroom platform. The results of the research show that the N-gain score is 81.6400, so the use of scientific literacy-based learning videos is effective on student learning outcomes. t-tests to students. Data analysis was carried out by determining N-Gain. The results showed that the N-Gain score was 0.8343 on high criteria and 83.43% on effective criteria., so the use of scientific literacy-based learning videos is effective on student learning outcomes.